2D metallic vanadium dichalcogenides and related heterostructures - Mongur Hossain; Hongmei Zhang; Ying Huangfu; Muhammad Zeeshan Saeed; Biao Qin; Dominik Bloos; Xidong Duan (Materials Today Advances, 2024)
Two-dimensional (2D) metallic transition metal dichalcogenides (TMDs) have garnered significant attention as promising candidates for various applications, including electronics, spintronics, and energy-related fields. Their appeal lies in their exceptional electronic conductivity, room-temperature ferromagnetism, charge density wave (CDW) phenomena, and catalytic properties, among other attributes. Among the diverse array of metallic TMDs, vanadium dichalcogenides (VX2, X = S, Se, and Te) stand out due to their distinctive set of physical and chemical properties. These properties have positioned VX2 materials at the forefront of both fundamental research and technological exploration in fields such as condensed matter physics, materials science, and device physics. In this comprehensive review, we present a thorough investigation of the recent advancements in 2D metallic VX2 materials and related heterostructures in the aspects of their structures, fabrication methods, key properties, and potential applications. First, the electronic and crystal structures of 2D VX2 are introduced. Second, the growth methods of VX2 and their heterostructures are discussed. Then, the novel physical properties and potential applications of 2D VX2 and its heterostructures are highlighted. Finally, we assess the current state of development in this growing field, acknowledging the obstacles ahead and the promising avenues for future research.